1995
DOI: 10.1002/j.1551-8833.1995.tb06422.x
|View full text |Cite
|
Sign up to set email alerts
|

Giardia and Cryptosporidium in raw and finished water

Abstract: The D/DBP Rule and the ESWTR must be orchestrated carefully to ensure protection of public health. The American Water System has conducted extensive monitoring of its operations since 1988. Analysis of 347 surface water samples collected between 1988 and 1993 showed that the prevalence rate of Giardia and Cryptosporidium was 53.9 percent and 60.2 percent, respectively. But because the parasite assay does not indicate viability or virulence, these results do not necessarily indicate that these water systems wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
1
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(86 citation statements)
references
References 14 publications
1
80
1
3
Order By: Relevance
“…That same study showed that 39% of filtered drinking water samples from these treatment plants contained C. parvum (27%) or G. lamblia (17%), although 78% of the plants met the turbidity requirements of the then-applicable Surface Water Treatment Rule (30). A subsequent study in 1995 still found 13% of finished treated water to be contaminated with Cryptosporidium oocysts (31). Correlations between increased rainfall and increased Cryptosporidium oocyst and Giardia cyst concentrations in river water have been reported (32).…”
Section: Drinking Watermentioning
confidence: 99%
“…That same study showed that 39% of filtered drinking water samples from these treatment plants contained C. parvum (27%) or G. lamblia (17%), although 78% of the plants met the turbidity requirements of the then-applicable Surface Water Treatment Rule (30). A subsequent study in 1995 still found 13% of finished treated water to be contaminated with Cryptosporidium oocysts (31). Correlations between increased rainfall and increased Cryptosporidium oocyst and Giardia cyst concentrations in river water have been reported (32).…”
Section: Drinking Watermentioning
confidence: 99%
“…Presently, there is a worldwide recommendation that systems serving populations between 10,000 and 100,000 people be required to monitor for presence of Giardia and Cryptosporidium in drinking water samples 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Cryptosporidium has been detected in marine mammals (Hughes-Hanks et al, 2005;Rengifo-Herrera et al, 2010) although their infectiousness to humans is poorly understood, however C.hominis has been detected in a dougon in Australia (Morgan et al, 2000). Outbreaks associated with contaminated drinking water have been reported world-wide (Fayer et al, 2004;LeChevallier and Moser, 1995).…”
Section: Data Linking Presence In Seawater To Food-borne Illnessmentioning
confidence: 99%
“…Giardia has been detected in marine mammals (Hughes-Hanks et al, 2005) although their infectious to humans in poorly understood. Outbreaks associated with contaminated drinking water have been reported world-wide (LeChevallier and Moser, 1995).…”
Section: Data Linking Presence In Seawater To Food-borne Illnessmentioning
confidence: 99%